Anxious times: medicine and modernity in nineteenth-century Britain - Bonea, Amelia; Dickson, Melissa; Shuttleworth, Sally; Wallis, Jennifer (Science and culture in the nineteenth century, 2019)
Intro -- Contents -- Acknowledgments -- Introduction -- 1. "The Influence of Employments on Health": Work and Medical Discourses about Occupational Health -- 2. Technologies of Modernity: Telegraphs, Telephones, and Medical Practice in the Nineteenth and Early Twentieth Centuries -- 3. Unhealthy Economies: Illness and Infection in British Coastal Resorts -- 4. The Woman Secret Drinker in the Late Nineteenth-Century Press -- 5. Knocking Some Sense into Them: Overpressure Debates and the Education of Mind and Body -- 6. Bringing Them Up to Speed: Nineteenth-Century Nervous Systems and Cultural Fantasies of Adaptation -- Conclusion -- Notes -- Bibliography -- Index.